Tocilizumab in patients hospitalised with COVID-19 pneumonia: Efficacy, safety, viral clearance, and antibody response from a randomised controlled trial (COVACTA). (May 2022) - Rosas, Ivan O.; Bräu, Norbert; Waters, Michael; Go, Ronaldo C.; Malhotra, Atul; Hunter, Bradley D.; Bhagani, Sanjay; Skiest, Daniel; Savic, Sinisa; Douglas, Ivor S.; Garcia-Diaz, Julia; Aziz, Mariam S.; et al.
Summary: Background: In COVACTA, a randomised, placebo-controlled trial in patients hospitalised with coronavirus disease-19 (COVID-19), tocilizumab did not improve 28-day mortality, but shortened hospital and intensive care unit stay. Longer-term effects of tocilizumab in patients with COVID-19 are unknown. Therefore, the efficacy and safety of tocilizumab in COVID-19 beyond day 28 and its impact on Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) clearance and antibody response in COVACTA were investigated. Methods: Adults in Europe and North America hospitalised with COVID-19 ( N  = 452) between April 3, 2020 and May 28, 2020 were randomly assigned (2:1) to double-blind intravenous tocilizumab or placebo and assessed for efficacy and safety through day 60. Assessments included mortality, time to hospital discharge, SARS-CoV-2 viral load in nasopharyngeal swab and serum samples, and neutralising anti-SARS-CoV-2 antibodies in serum. ClinicalTrials.gov registration: NCT04320615. Findings: By day 60, 24·5% (72/294) of patients in the tocilizumab arm and 25·0% (36/144) in the placebo arm died (weighted difference –0·5% [95% CI –9·1 to 8·0]), and 67·0% (197/294) in the tocilizumab arm and 63·9% (92/144) in the placebo arm were discharged from the hospital. Serious infections occurred in 24·1% (71/295) of patients in the tocilizumab arm and 29·4% (42/143) in the placebo arm. Median time to negative reverse transcriptase–quantitative polymerase chain reaction result in nasopharyngeal/oropharyngeal samples was 15·0 days (95% CI 14·0 to 21·0) in the tocilizumab arm and 21·0 days (95% CI 14·0 to 28·0) in the placebo arm. All tested patients had positive test results for neutralising anti–SARS-CoV-2 antibodies at day 60. Interpretation: There was no mortality benefit with tocilizumab through day 60. Tocilizumab did not impair viral clearance or host immune response, and no new safety signals were observed. Future investigations may explore potential biomarkers to optimize patient selection for tocilizumab treatment and combination therapy with other treatments. Funding: F. Hoffmann-La Roche Ltd and the US Department of Health and Human Services, Office of the Assistant Secretary for Preparedness and Response, Biomedical Advanced Research and Development Authority, under OT number HHSO100201800036C.